GENESIS AND COMPOSITION OF LAZURITE IN MAGNESIAN SKARNS - Aleksandrov S.M.; Senin V.G. (My University, 2006)
The genesis and composition of lazurite was considered in the metasomatic rocks and deposits of the Baikal area, Pamirs, Hindu Kush, and other regions. It was shown that formation of lazurite is related to the prograde bimetasomatic or contact-metasomatic magnesian skarn processes developing in dolomites. The skarnized sedimentary or metamorphic rocks should be salt-bearing, contain sulfur-bearing minerals, and be affected by Cl-bearing hydrothermal solutions. Both abyssal and hypabyssal skarn bodies show distinct zoning. Depending on the PT parameters, their metasomatic columns can vary, with the preservation of the Mg/Ca ratio from the carbonate precursor. The formation of contact-metasomatic lazurite mineralization is promoted by high-alkali magmatic solutions, which cause the replacement of dolomites by skarn. Lazurite can also be formed during the postmagmatic stage, owing to a change in the mineral composition of the adjacent aluminosilicate and magnesian-skarn rocks at abyssal and hypabyssal deposits around the world. The occurrence of authigenic lazurite emphasizes its polygenetic formation. © Pleiades Publishing, Inc. 2006.
Keywords: lazurite